Impact of pretreatment with intravenous thrombolysis on reperfusion status in acute strokes treated with mechanical thrombectomy. (14th May 2019) - Goyal, Nitin; Tsivgoulis, Georgios; Pandhi, Abhi; Malhotra, Konark; Krishnan, Rashi; Ishfaq, Muhammad F; Krishnaiah, Balaji; Nickele, Christopher; Inoa-Acosta, Violiza; Katsanos, Aristeidis H; Hoit, Daniel; Elijovich, Lucas; et al.
Abstract : Introduction: We sought to evaluate the impact of pretreatment with intravenous thrombolysis (IVT) on the rate and speed of successful reperfusion (SR) in patients with emergent large vessel occlusion (ELVO) treated with mechanical thrombectomy (MT) in a high-volume tertiary care stroke center. Methods: Consecutive patients with ELVO treated with MT were evaluated. Outcomes were compared between patients who underwent combined IVT and MT (IVT+MT) and those treated with direct MT (dMT). The elapsed time between groin puncture to beginning of reperfusion (GPTBRT) and the numbers of device passes required to achieve SR were also documented. Results: A total of 287 and 132 patients were treated with IVT+MT and dMT, respectively. The IVT+MT group had higher SR (73.8% vs 62.9%; p=0.023) and 3-month functional independence (modified Rankin Scale score 0–2;51.6% vs 38.2%; p=0.008) rates. The median GPTBRT was shorter in the IVT+MT group (48 (IQR 33–70) vs 70 (IQR 44–98) min; p<0.001). Among patients who achieved SR (n=292), the median number of required device passes was lower in the IVT+MT subgroup (1 (IQR 1–1) vs 2 (IQR 1–2); p<0.001), while the rate of patients requiring ≤2 device passes was higher (98% vs 77%; p<0.001). IVT+MT was independently related to higher odds of SR (OR 1.64; 95% CI 1.03 to 2.61; p=0.036) and shorter GPTBRT (unstandardized linear regression coefficient −20.39; 95% CI −27.56 to –13.22; p<0.001) on multivariable analyses adjusting for potential confounders. Among patients with SR, IVT+MT was independently associated with a higher likelihood of ≤2 device passes (OR 14.63; 95% CI 4.46 to 48.00; p<0.001). Conclusions: IVT pretreatment appears to increase the rates of SR and shortens the duration of the endovascular procedure by requiring fewer device passes in patients with ELVO treated with MT.